Assessment of quality of life among elderly population of rural areas of Etawah district: a cross sectional study - Bansal, Priyanka; Dixit, Anand M.; Jain, Pankaj K.; Gupta, Sandip K.; Bajpai, Prashant K.; Mehra, Jyoti (International Journal Of Community Medicine And Public Health, 2019)
Background: All the aspects of health status, lifestyle, life satisfaction, mental health and well-being together reflects the multidimensional nature of quality of life (QOL) in an individual. The objective of the study was to assess the quality of life among rural elderly population of Etawah district and their association with various socio demographic factors. Methods: A community based cross-sectional study was conducted among 316 elderly subjects in rural areas of Etawah district. QOL was assessed by using WHOQOL-OLD tool. Socio-demographic factors were assessed by using a self-structured questionnaire. Data was analysed by using Microsoft Excel 2010 and statistical software SPSS-22. Transformed facet sore were calculated using WHOQOL- OLD manual and Independent sample t- test were applied. Results: Majority (86%) were in the (≤75) years of age. Among the study participants, 52.8% were females, 67.5% were illiterate, 72.5% belong to nuclear family. The mean scores of QOL domains was maximum in death and dying (83.20), followed by sensory ability (62.99).The lowest mean score was seen Intimacy domain (22.80). Gender, type of family, financial status and staying with partner were found to be the determinants of better QOL (p>0.05). Conclusions: The mean quality of life score was below average in intimacy domain. It was maximum in death and dying domain.